Pre-service ESL teachers engaging in Reflective Practice: Current observations and Perceived Challenges - Ong, Wei Ann; Suyansah Swanto; Asmaa Al Saqqaf (2018)
This study aims to present the observations and perceived challenges of a group ofEnglish as a Second Language (ESL) pre-service teachers (PSTs) engaging in reflectivepractice in their practicum. Past studies have shown that PSTs are uncapable of reflectingon their practice at the critical level. Results from the online survey indicated thatreflection thinking is one of the areas respondents opined that they need to improve.Analysis of their practicum reflection forms indicated a low level of reflection shown bythe respondents as they reflect on their lessons. Follow-up focus group interviews on therespondents’ reflective thinking revealed that respondents lack a clear grasp of whatreflective thinking is about, and they also expressed their reluctance of reflecting withtheir peers on their lessons. The outcome of this study precipitates a need for PSTs tolearn a strategy to conduct a critical reflection. Subsequently, it could be beneficial forthe respondents to capitalise on peer feedback via an online platform as a means ofimproving their practice as ESL teachers.